Teacher training at the university - Barriga Hernández, Carlos (2014)
This article is the first in a series the author is preparing. It addresses the issue of professional academic training at university level. In part it formulates a conception of the university based on three basic principles: autonomy, democracy and meritocracy. This gives to university training a specific character compared to other high education centers. This first table of ideas is completed pointing to the three main objectives of the university. On this ideological basis is conducted an analysis of the professional academic training, showing their guidelines and levels, content areas of university education as well as defining what is a profession epistemologically and its implications for education and pedagogy.